The Role Of Islamic Religious Education In The Era Of Information And Communication Technology - Jimi Harianto (Sharia Journal and Education Center Publishing, 2024)
Abstract In the era of globalization, the role of information and communication technology has become very strategic because it presents a world without borders, distance, space and time, and is effective in increasing productivity and efficiency. The Islamic religious education learning process can obtain information, manipulate, manage and exchange knowledge or exchange information more easily. The integration of ICT in educational programs will play an important role in developing students' thinking and developing skills. Increasing teacher professionalism in ICT activities, especially the use of ICT platforms in PAI classes, in order to improve learning and make the education center a center for creative learning, as well as motivation so that students can understand and motivate themselves in learning PAI. In the educational field, ICT programs aim to familiarize students with common ICT information and tools, including computers. Students are expected to understand the terms used in information and communication technology. Apart from helping students learn, the role of information and communication technology inside Education is very influential for teachers, especially in utilizing opportunities to improve teaching strengths. Keywords: Islamic Religious Education and Information Technology Abstrak Di era globalisasi, peran teknologi informasi dan komunikasi menjadi sangat strategis karena menghadirkan dunia tanpa batas, jarak, ruang dan waktu, serta efektif dalam meningkatkan produktivitas dan efisiensi. Proses pembelajaran pendidikan agama Islam dapat memperoleh informasi, memanipulasi, mengelola dan bertukar pengetahuan atau bertukar informasi dengan lebih mudah. Integrasi TIK dalam program pendidikan akan memainkan peran penting dalam mengembangkan pemikiran siswa dan mengembangkan keterampilan. Peningkatan profesionalisme guru dalam kegiatan TIK khususnya penggunaan platform TIK di kelas PAI, guna meningkatkan pembelajaran dan menjadikan pusat pendidikan sebagai pusat pembelajaran yang kreatif, serta motivasi agar peserta didik dapat memahami dan memotivasi diri dalam belajar PAI. Dalam bidang pendidikan, program TIK bertujuan untuk membiasakan siswa dengan informasi dan alat TIK yang umum, termasuk komputer. Siswa diharapkan dapat memahami istilah-istilah yang digunakan dalam teknologi informasi dan komunikasi. Selain membantu siswa belajar, peran teknologi informasi dan komunikasi di dalam dunia pendidikan sangat berpengaruh bagi para guru, terutama dalam memanfaatkan peluang untuk meningkatkan kemampuan mengajar. Kata Kunci: Pendidikan Agama Islam dan Teknologi Informasi